Pemanfaatan Lahan Pekarangan dengan Tanaman Bumbu Dapur Berkhasiat untuk Kesehatan di Kecamatan Mojolaban, Kabupaten Sukoharjo - Umi Barokah; Wiwit Rahayu; Ernoiz Antriyandarti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Wirun Village as a tourist village needs to be beautified, especially residents’ houses that are also the destination for the tourists. At the same time, the households in Wirun Village need to be developed in their economic capacity and food self-sufficiency. One of them is by utilizing the yard area by planting kitchen spices that can be used for condiment necessities. This community service program is implemented in Mojolaban Sub-district, Sukoharjo District with the target of PKK community in Wirun Village. In an effort to utilize the yard, activities in this community service are: (1) counseling about cultivation and the benefit of kitchen spices with health efficacy and (2) facilitating the procurement of seeds (bay leaves, kaffir lime, bilimbi, and basil) and growing media. This activity will increase PKK members knowledge about cultivation, health benefits, and economic benefits from cultivating kitchen spices with health efficacy. The infrastructure provided by the community will be used for implementing the counseling results by planting kitchen spices with health efficacy in the yard area of each PKK member. The continuation of this activity is supported by Wirun Village government by providing an area for a pilot project to cultivate kitchen spices with health efficacy.